PERANCANGAN SISTEM INFORMASI AKUNTANSI TERKOMPUTERISASI ATAS SIKLUS PENYEWAAN DAN PERSEDIAAN DENGAN MENGGUNAKAN MICROSOFT SQL SERVER 2005 DAN BORLAND DELPHI 2007 PADA CV. ASTA KARYA JAYA - HARTONO, RUDI (Jurnal Akuntansi AKUNESA, 2016)
In the system of renting and inventory CV. Asta Karya Jaya running currently still using a manual system. With the change of system in CV. Asta Karya Jaya which was originally used to manually turns into a computerized has its own benefits for CV. Asta Karya Jaya which can increase the speed of data retrieval on the activities of renting and supplies company, converting data into information so that management can plan, execute, control and evaluate the activities of renting and supplies for decision-making, and provide adequate controls to safeguard corporate data. This research can be expected from renting system has been arranged in a computerized so as to reduce the weaknesses that exist in the old system in CV. Asta Karya Jaya. Keywords: Database, Renting, Computerized.